Responses of the trunk routes of a harvester ant to plant density - Lopez, F; Acosta, F J; Serrano, J M (Oecologia, 1993)
Messor barbarus is a Mediterranean harvester ant that constructs physically defined trunk routes on the ground to connect nest entrances with foraging areas. Some responses of these trunk routes to plant density (and therefore resource abundance) were analyzed by testing the preferential allocation of different parts (trunk route ends, segments and branching points) in a patchy environment. Maps of grass density in four categories and Messor barbarus trunk routes were compiled for a Mediterranean pasture in Central Spain over four con- secutive years. The proportions of the density categories in each year were used to calculate random expected fre- quencies of the trunk route points and the predominance of higher or lower grass densities. Trunk route ends discriminate and selectively reach patches with a greater abundance of resources in all study years. Branching points are also allocated preferentially in areas with higher vegetation density, but only in years with a predom- inance of the higher categories of grass density. In these years, the colonies of Messor barbarus have a "phalanx" strategy at a colonial level, and branching is more profuse. Finally, trunk route segments do not indicate any preference for crossing determined vegetation den- sities, but rather connect successive branching points or trunk route ends by the shortest route. These results concur with a model of structural strategy change ("guerilla" - "phalanx") (Hutchings 1988) at the level of trunk routes. They are probably constituted by "tran- sitory" sections with few branches, that expand other more profusely branched sections which are more dedi- cated to foraging.
Keywords: Guerilla; Harvester ants; Messor barbarus; Phalanx; Trunk routes